Evaluation of parasitological and monoclonal antibody based assays in detection of Trypanosoma evansi infection in animals - RAYULU, V C; CHAUDHRI, S S; SINGH, A (The Indian Journal of Animal Sciences, 2011)
Blood samples from naturally infected, suspected and healthy cattle (826), buffaloes (285), equines (395) and camels (32) from different places of Haryana were collected and examined for the detection of Trypanosoma evansi infection with parasitological tests (wet blood film, WBF; microhaematocrit technique, MHCT) and monoclonal antibody based antigen detection assays (Enzyme linked assays, Ag-ELISA; latex agglutination test, Ag-LAT). Trypanosoma evansi infection was detected in 3.0 and 6.1%, 0.7 and 1.1%, and 2.8 and 3.0% cattle, buffaloes and equines with WBF and MHCT, respectively. The camels (32) examined during the period of study were found negative for T. evansi infection with WBF and MHCT. Species-wise, T.evansi antigens were detected in 50.73 and 40.92% cattle, 37.19 and 30.18% buffaloes, 31.90 and 27.85% equines and 12.5% camels with Ag-LAT and Ag-ELISA, respectively. Latex agglutination proved more sensitive than the ELISA. The former assay also detected 50 positive out of 53 MHCT positive bovine samples in comparison to 46 detected by ELISA. The screening of MHCT positive bovine serum samples (35) with CIC-ELISA detected T. evansi immune complexes in 34 whereas Ag detection ELISA failed to reveal T.evansi antigens in 7 MHCT positive samples. These observations made it clear that CIC-ELISA is a better option than indirect Ag- ELISA and Ag-LAT is a rapid and field applicable test to arrive at a decision to undertake chemotherapeutic measures in surra-suspected animals.